2008
DOI: 10.1037/0735-7044.122.1.191
|View full text |Cite
|
Sign up to set email alerts
|

Handedness for tool use correlates with cerebellar asymmetries in chimpanzees (Pan troglodytes).

Abstract: Recent studies have shown that great ape species possess patterns of macrostructural neocortical asymmetries that are similar to those found in humans. However, little is known about the asymmetry of subcortical structures in great apes. To address this lack of data, the authors assessed left-right asymmetry of the anterior and posterior aspects of cerebellum from MRI brain scans of 53 chimpanzees (Pan troglodytes). No population-level bias was found for either the anterior or the posterior region of the cereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 57 publications
2
12
0
Order By: Relevance
“…The results from comparing right-and left-handed throwers also support this conclusion, because differences in WM are hemisphere-specific and contralateral to the preferred hand that the chimpanzees use for throwing. The association between hand preferences for throwing and asymmetries within the IFG and KNOB are also consistent with previous studies showing that handedness for other forms of tool use, such as simulated termite-fishing and nutcracking, is linked to lateralization in the cortical language area homologues of chimpanzees [33,44]. It should also be noted that asymmetries in hand use for manual gestures are associated with asymmetries within the IFG [45] Thus, the results reported here are consistent with the evolutionary hypothesis that throwing may have served as a preadaptation for the neural adaptation of motor programmes necessary for complex motor actions, including language and speech [11].…”
Section: Discussionsupporting
confidence: 91%
“…The results from comparing right-and left-handed throwers also support this conclusion, because differences in WM are hemisphere-specific and contralateral to the preferred hand that the chimpanzees use for throwing. The association between hand preferences for throwing and asymmetries within the IFG and KNOB are also consistent with previous studies showing that handedness for other forms of tool use, such as simulated termite-fishing and nutcracking, is linked to lateralization in the cortical language area homologues of chimpanzees [33,44]. It should also be noted that asymmetries in hand use for manual gestures are associated with asymmetries within the IFG [45] Thus, the results reported here are consistent with the evolutionary hypothesis that throwing may have served as a preadaptation for the neural adaptation of motor programmes necessary for complex motor actions, including language and speech [11].…”
Section: Discussionsupporting
confidence: 91%
“…Various studies suggest that handedness in great apes may be linked to posture and/or tool use (Olson et al, 1990; Hopkins, 1993; Hopkins et al, 2007; Cantalupo et al, 2008). Several previous studies report a right-hand bias when in bipedal versus quadru-pedal posture in all four great ape species, but none of them directly examined bipedal tool use.…”
Section: Discussionmentioning
confidence: 99%
“…In studies of chimpanzees, we have previously found that variation in handedness for tool use, but not other motor actions, are associated with lateralization in the cerebellum [Cantalupo et al, 2008]. More recently, we have also found that chimpanzees who have learned to reliably throw have significantly larger cerebella than chimpanzees who do not throw, suggesting that experiential factors can influence the size of the cerebellum or alternatively, that certain patterns of neural organization within the cerebellum facilitate the acquisition of certain motor skills [Cantalupo & Hopkins, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…Although the tracers were not blind to the species of the apes, they were blind to the hypotheses of the study. Before collection of the data, inter-rater reliability in the measurement of each brain region was established between two raters [Cantalupo et al, 2003, 2008; Freeman et al, 2004; Hopkins & Cantalupo, 2004]. To assess inter-rater reliability, two individuals measured all both brain regions for ten individual chimpanzees.…”
Section: Methodsmentioning
confidence: 99%